Lateral crushing of composite fuselages - Syed Mohamed Ali, Jaffar; Shahidan, Zul Hasyimi (IIUM Press, 2011)
Lateral crushing experiment on a model of a composite based-fuselage of Unmanned Aerial Vehicle (UAV) has been carried out. The middle cylindrical part of the fueslage was selected as the area of interest. The model was fabricated using Carbon fiber/epoxy by means of hand lay-up method and was put under quasi-static compression loading in order to simulate the impact forces during a crush event. The energy absorption per unit volume of the composite material was obtained from the force vs. displacement graph obtain.